Evaluation of autonomous recording units for detecting 3 species of secretive marsh birds - Anna M. Sidie‐Slettedahl; Kent C. Jensen; Rex R. Johnson; Todd W. Arnold; Jane E. Austin; Joshua D. Stafford (Wildlife Society Bulletin)
ABSTRACT Population status and habitat use of yellow rails (Coturnicops noveboracensis), Nelson's sparrows (Ammodramus nelsoni), and Le Conte's sparrows (A. leconteii) are poorly known, so standardized surveys of these species are needed to inform conservation planning and management. A protocol for monitoring secretive marsh birds exists; however, these species regularly call at night and may be missed during early morning surveys. We tested the effectiveness of autonomous recording units (hereafter, recording units) to survey these species by analyzing recorded vocalizations using bioacoustics software. We deployed 22 recording units at 54 sites in northern Minnesota and eastern North Dakota, USA, and conducted traditional broadcast surveys during May–June, 2010 and 2011. We compared detection probabilities between recording units and standard monitoring protocols using robust‐design occupancy models. On average, recording units detected 0.59 (SE = 0.11) fewer Le Conte's sparrows, 0.76 (SE = 0.15) fewer Nelson's sparrows, and 1.01 (SE = 0.14) fewer yellow rails per survey than were detected using the standard protocol. Detection probabilities using the standard protocol averaged 0.95 (yellow rail; 95% CI = 0.86–0.98), 0.93 (Le Conte's sparrow; 95% CI = 0.78–0.98), and 0.89 (Nelson's sparrow; 95% CI = 0.56–0.98), but averaged 0.71 (yellow rail; 95% CI = 0.56–0.83), 0.61 (Le Conte's sparrow; 95% CI = 0.42–0.78), and 0.51 (Nelson's sparrow; 95% CI = 0.19–0.82) using recording units. Reduced detection by recording units was likely due to the ability of human listeners to identify birds calling at greater distances. Recording units may be effective for surveying nocturnal secretive marsh birds if investigators correct for differential detectability. Reduced detectability may be outweighed by the increased spatial and temporal coverage feasible with recording units. © 2015 The Wildlife Society.